Utility of GDF‐15 as a diagnostic biomarker in gastric cancer: an investigation combining GEO, TCGA and meta‐analysis - Liu, Jie‐yu (FEBS Open Bio, 2018)
It was recently suggested that growth differentiation factor‐15 (GDF‐15) is associated with gastric cancer (GC) carcinogenesis. However, the diagnostic potential of GDF‐15 for GC remains unclear. To address this issue, we obtained RNA sequencing and microarray data from the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases, and searched PubMed, Google Scholar and Web of Science for relevant literature. We then used STATA to perform a meta‐analysis. In total, reports of 253 GC patients and 112 healthy controls who contributed peripheral blood samples were taken from the four literature sources, while information on 754 GC tumor and 263 gastric normal tissues was drawn from TCGA and seven GEO datasets. The expression level of GDF‐15 mRNA was significantly higher in tumor tissues than in normal tissues, with a standard mean difference (SMD) of 0.79% and a 95% confidence interval (95% CI) of 0.63–0.95. Consistently, the GDF‐15 protein in blood was significantly increased in GC patients as compared to controls (SMD  = 3.74, 95% CI = 1.81–5.68). In addition, based on information from TCGA and GEO datasets, the expression level of GDF‐15 mRNA may be of use for the diagnosis of GC, with a combined sensitivity, specificity and odds ratio of 0.69 (95% CI = 0.58–0.79), 0.90 (95% CI = 0.84–0.93) and 6.32 (95% CI = 4.22–9.49), respectively. The summary receiver operating characteristic curve demonstrated that the area under the curve was 0.90 (95% CI = 0.87–0.93). The results suggest higher levels of GDF‐15 may be associated with GC tumorigenesis and may have the potential to be a diagnostic biomarker of GC.